(untitled) (Nexo Revista Científica, 2021)
Increasing the penetration level of distributed generation units as well as power electronic devices adds more complexity and variability to the dynamic behavior of the microgrids. For such systems, studying the transient modelling and stability is essential. One of the major disadvantages of most studies on microgrid modelling is their excessive attention to the steady state period and the lack of attention to microgrid performance during the transient period. In most of the research works, the behavior of different microgrid loads has not been studied. One of the mechanisms of power systems stability studies is the application of state space modelling. These studies include the development of state space models of various components of the power system and then linearizing them around an equilibrium point. In this paper, a comprehensive method for modelling of islanded microgrid with dynamic and static loads is presented. The basic step of the proposed method is transformation to a dq0-based model. In order to find a complete and accurate model of islanded inverter-based microgrid, the sub-modules of generation, network and load must be modelled in local dq reference and then transferred to a common reference. The simulation results show the effectiveness of the proposed modelling approach for transient stability studies.